2023
DOI: 10.1002/psp.2643
|View full text |Cite
|
Sign up to set email alerts
|

Does social exposure influence locals' and migrants' city attachment? Comparing residential areas and activity spaces

Abstract: City attachment captures individual migrants' emotional bonds to their host city and is an essential indicator of their social integration. Although a growing literature has investigated the impact of the residence-based social environment on city attachment, few works have attempted to unravel the effects of social exposure in an individual's daily activity space. Drawing on an activity diary survey and census data from Shanghai, we examine how social exposure in residential areas and activity spaces influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Therefore, residential segregation at the neighbourhood level can negatively impact health outcomes through the mechanism of relative deprivation. Another study (Lin and Ta, 2023) suggests evaluating social mix in residential and routine activity locations as it plays a crucial role in individual’s experiences of city attachment and their subsequent social integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, residential segregation at the neighbourhood level can negatively impact health outcomes through the mechanism of relative deprivation. Another study (Lin and Ta, 2023) suggests evaluating social mix in residential and routine activity locations as it plays a crucial role in individual’s experiences of city attachment and their subsequent social integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, as activity space-based segregation may also affect individuals’ life satisfaction, subjective well-being, and social integration, these issues need to be analyzed in depth (Lin and Ta, 2023; Wang et al, 2019). Based on a study conducted in Hong Kong, Wang et al (2019) found that social comparisons in both residential areas and daily activity spaces may contribute to individual life satisfaction.…”
Section: Challenges and Future Studiesmentioning
confidence: 99%
“…Based on a study conducted in Hong Kong, Wang et al (2019) found that social comparisons in both residential areas and daily activity spaces may contribute to individual life satisfaction. Another study in Shanghai found that rural migrants’ city attachment is significantly influenced by the social environment within their activity space (Lin and Ta, 2023). The mechanisms of these activity space effects may arise from accessibility to various facilities and resources in the activity space, spatiotemporal contact with different groups, and so on.…”
Section: Challenges and Future Studiesmentioning
confidence: 99%